Manajemen Pembelajaran Bahasa Berbasis Integrasi-Interkoneksi Menuju World Class University - Musthofa, Tulus; Setiyawan, Agung; Sodiq, M. Ja’far (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
Maulana Malik Ibrahim State Islamic University Malang is is known as a succesfull campusin running foreign languages learning, especially Arabic. This research aimed tocompare the management of Arabic language learningin UIN Maliki and UIN SunanKalijaga to generate some feed backs in improving the quality of language learningas wellas an effort towards world class university. The result of research showed theadvantages of each university in running arabic learning. UIN Maliki Malang focuses onoptimizing arabic learning in dormitory (ma’had) with a variety of language activities,while UIN Sunan Kalijaga Yogyakarta focuses on integrating scientific material andarabic language.